Geopolitik Perbatasan Indonesia–Malaysia: Studi Kasus Konflik Ambalat - Prihatna, Dwi; Nazori, Nauval; Zidan, Yazid; Nurlia, Elly (Media Hukum Indonesia (MHI), 2025)
The This study analyzes the geopolitics behind the Ambalat Block dispute between Indonesia and Malaysia using a descriptive qualitative approach and a literature review (2019–2025). The study examines historical context, international legal frameworks, domestic political influences, resource-driven incentives (oil and gas), and dispute-settlement options including bilateral negotiation, arbitration, and joint development. Findings indicate that economic interests, domestic politics, and technical uncertainties necessitate pragmatic cooperative mechanisms such as joint development and strengthened maritime legal documentation. Recommendations include comprehensive baseline registration, enhanced technical diplomacy, and inter-agency confidence-building